The Enactment of Performance Assessment in Teaching Writing: A Case Study at SMAN 2 Semarang - Lia Elyani Sukawatie (Universitas Muhammadiyah Semarang, 2018)
The application of curriculum 2013 in Indonesia becomes controversy in Indonesia. For senior high school students, the 2013 curriculum gives them opportunity to learn another subjects from the other major such as science students can learn about economics. This is also happened to English subject. There are two types of English subject; compulsory English and supplementary English. Both of them have different syllabus and assessment. The important of assessment is to show how the students’ understanding and the teacher’s perspective to the curriculum. In this research, the researcher observes SMA Negeri 2 Semarang and it is specify to X grade science. This research focus on performance assessment especially in writing. It is chosen because writing can reflect the grammar understanding which is very important to do the compulsory test such as final term test and National Examination. Besides, the assessment can reflect the teacher’s method effectiveness. The writer collected the data by using observation, interview, and documentation. The data was collected in March 2018 with the English teacher of grade X. The interview involved the English teacher, the principal, and the vice principal of curriculum. The documents are syllabus, lesson plans, and the students’ assessment. The research shows that the implementation of 2013 curriculum by the English teacher can be seen from the assessment of the students. The students’ skill as targeting in 2013 curriculum is achieved. This happened since the student center method applied in the class. So, the students are more active rather than the teacher. The barriers are finding the right method and the right instrument of authentic assessment. They both are important to support the success of Core and Basic Competence realization in the learning.